Socialization of Stingless Bee Cultivation for Economic Empowerment of West Payakumbuh Community, Payakumbuh City, West Sumatra - Cori Qamara; I Putu Gede Didik Widiarta; Amalina Nur Wahyuningtyas; Amani Aldiyanti (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
This activity aims to strengthen the local economy in West Payakumbuh, Payakumbuh City, West Sumatra, by implementing community service related to stingless bee beekeeping socialization. In addition to promoting environmental conservation, this program seeks to raise community awareness of stingless bee beekeeping's potential as a sustainable alternative source of income. Technical instruction in stingless bee beekeeping, processing bee products including honey and propolis, and marketing these goods are used to carry out socialization activities. The findings demonstrated the community's strong passion and ability to successfully implement stingless bee beekeeping techniques, particularly among farmers and breeders. Products from stingless bee bees also have a lot of commercial potential and can lower reliance on the traditional economic sector while also enhancing community welfare. Micro-enterprises based on bee products can also be developed thanks to this training, which should hasten the sustained economic empowerment of communities. In general, this service was successful in promoting the establishment of an eco-friendly company and contributing to the rise in the income of Payakumbuh City residents.